PENGARUH PEMBERIAN KOMBINASI FLY ASH DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays L. saccharata Sturt) VARIETAS PARAGON TANAH ULTISOL - Amanda, Nesya Amelia; Agustini, Rika Yayu; Subardja, Vera Oktavia (Jurnal Ilmiah Hijau Cendekia, 2025)
Fly ash waste that contains a lot of minerals can be combined with goat manure to improve soil texture, so it can help increase the growth and yield of Sweet Corn plants (Zea mays L. saccharata Sturt). The study aimed to determine the effect of real differences and the best dose of the combination of fly ash and goat manure on the growth and yield of sweet corn plants (Zea mays L. saccharata Sturt) ultisol soil paragon varieties. The research was carried out on land owned by the Republic of Indonesia Money Printing Company (PERURI) from December 2023 to February 2024. The method used is an experimental method using a single-factor Group Random Design (RAK) with 12 treatments and 3 repeats, so that there are 36 experimental units consisting of: A (Control), B (Goat manure 10 ton/ha), C (Goat Manure 20 ton/ha, D (Fly Ash 15 ton/ha), E (Fly Ash 15 ton/ha + Goat Manure 10 ton/ha), F (Fly Ash 15 ton/ha + Goat Manure 20 ton/ha), G (Fly Ash 20 ton/ha), H (Fly Ash 20 ton/ ha + Goat Manure 10 ton/ha), I (Fly Ash 20 ton/ha + Goat Manure 20 ton/ha), J (Fly Ash 25 ton/ha), K (Fly Ash 25 ton/ha + Goat Manure 10 ton/ha), L (Fly Ash 25 ton/ha + Goat Manure 20 ton/ha). The results showed that the treatment had a real effect on plant growth and yield. Fly Ash Treatment 20 ton/ha + Goat Manure 20 ton/ha (I), gives the highest yield of sweet corn plants (187.00 cm), Stem Diameter (27.13mm), Number of leaves (14.67 strands), Wet stash weight (657.00 grams), Cob Length (28.97 grams), Cob Diameter (62.93 mm), Cob weight with cob (516.00 grams) Without cob (394.00 grams) and Number of Cob Seed Rows (15.33 rows). Keywords: Fly Ash, Goat Manure, Sweet Corn and Ultisol